2022
DOI: 10.1530/ec-21-0506
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and quality of life among thyroid cancer survivors without persistent or recurrent disease

Abstract: Background: Cancer-related fatigue is one of the most important issues for patients, but research on this topic is sparse. This study aimed to determine the prevalence of fatigue in postoperative patients with papillary thyroid carcinoma (PTC) and to identify the clinical features associated with fatigue. Methods: We conducted a cross-sectional study on 292 thyroid cancer survivors. Fatigue and quality of life were the study outcomes, measured using the Cancer Fatigue Scale (CFS) and the SF-36 version 2.0. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…Most studies previously evaluated HRQoL according to treatment modality in only thyroid cancer survivors without comparative data and focused on depression, anxiety, fatigue, and concern about recurrence of thyroid cancer. Some articles evaluated HRQoL without valid tools or normative data [ 9 - 11 , 15 ]. After developing, validating, and translating questionnaires such as the EQ-5D [ 41 ], Thyroid Cancer Survivors’ Association (ThyCA)QoL [ 42 ], Thyroid-Specific Patient Reported Outcome (ThyPRO) [ 43 ], and European Organization for Research and Treatment of Cancer (EORTC)-Quality of Life Questionnaire-30 (EORTC-QLQ-C30) [ 44 ], several studies have adapted these tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies previously evaluated HRQoL according to treatment modality in only thyroid cancer survivors without comparative data and focused on depression, anxiety, fatigue, and concern about recurrence of thyroid cancer. Some articles evaluated HRQoL without valid tools or normative data [ 9 - 11 , 15 ]. After developing, validating, and translating questionnaires such as the EQ-5D [ 41 ], Thyroid Cancer Survivors’ Association (ThyCA)QoL [ 42 ], Thyroid-Specific Patient Reported Outcome (ThyPRO) [ 43 ], and European Organization for Research and Treatment of Cancer (EORTC)-Quality of Life Questionnaire-30 (EORTC-QLQ-C30) [ 44 ], several studies have adapted these tools.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that thyroid cancer survivors experience physical or psychological distress [9][10][11][12][13][14]. These studies had small sample sizes and short-term follow-up period [10,11,13] or lacked a healthy control group [9][10][11][12]15]. These studies also lacked valid tools to evaluate health-related (HR) QoL [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have hypothesized that a high level of free T3 is associated with altered physical performance and fatigue in DTC survivors undergoing TSH suppression. They suggest considering thyroid functional status, particularly the level of free T3, to alleviate the burden on HRQoL ( 37 ). The recent trend of individualizing treatment and avoiding aggressive interventions in low-risk cases of thyroid cancer is expected to have a positive impact on the HRQoL of long-term survivors ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The scale has a high sensitivity and specificity and usually set a cut-off value of 19 to identify fatigue in cancer patients. 16 …”
Section: Methodsmentioning
confidence: 99%
“…15 The cancer fatigue scale (CFS) is a 15-item scale used to assess fatigue in cancer patients with a total score ranging from 0 (no fatigue) to 60 (maximum). 16 The scale has 3 subscales including physical (maximum score of 28), affective (maximum score of 16), and cognitive (maximum score of 16). The scale has a high sensitivity and specificity and usually set a cut-off value of 19 to identify fatigue in cancer patients.…”
mentioning
confidence: 99%